Die krag van simbole en rites in die liturgie - Vos, C. J. A. (Faculty of Theology, University of the Free State, 2005)
Engish: There is an old and dynamic relationship between cult and context. This relationship implies that worship is not experienced in a void. A contextual approach must take into consideration the rise and fall of post-modern saints, where the power of symbols can also be seen. This article considers liturgy as a creative process. The liturgical meaning of symbols are also investigated. There is a specific focus on the symbolism of the Holy Communion. The focus also falls on the Kyrie, the Gloria and the Agnus Dei. Reformed liturgy has placed the Kyrie and the Gloria amongst confessions and mercy declarations. The Kyrie and the Gloria are entwined, and this can be seen in the invocation of commiseration that flows out into the praise of the commiseration. This article states the case for the use of Kyrie, the Gloria and the Agnus Dei during Holy Communion.
Keywords: Rituals; Symbols; Liturgy